PANCASILA DALAM KONTEKS SEJARAH PERJUANGAN BANGSA INDONESIA - Purwanta, Hieronymus (Candi, 2018)
This study aims to explore the root of Pancasila as national ideology of Indonesia. Two research questions arised: 1) what kind of cultural root of Pancasila in the life of Indonesian people; 2) what kind of processes of Indonesian leaders in formulating Pancasila. Method used was documentary study, both primary and secondary documents. The results show that many parts of Pancasila have to be culture of Indonesian. On the other hand, reconstruction of formulating Pancasila has to be deviated by political power of interest group. Nugroho Notosusanto as the New Order historian wanted to de-Soekarno-ization through heroificated Muhammad Yamin as Pancasila discoverer.